2006
DOI: 10.1540/jsmr.42.1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of TRP channels to the pacemaker activity of interstitial cells of Cajal in the gastrointestinal tract

Abstract: Interstitial cells of Cajal (ICCs) are a fundamental component of the pacemaker apparatus of the gastrointestinal (GI) tract. They have special properties that make them unique in their ability to generate and propagate slow waves in gastrointestinal smooth muscle. The pacemaker current that generates slow waves is initially due to a voltageindependent, Ca 2+ -inhibited, non-selective cationic conductance in ICC. The classical transient receptor potential (TRPC) channel 4 was suggested as a molecular candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Furthermore, in interstitial cells of Cajal, TRPC4 was suggested as a molecular candidate for the nonselective cation channel responsible for the pacemaker activity (14). In the entorhinal cortex, TRPC cation channels mediating persistent muscarinic currents contribute significantly to the firing and mnemonic properties of projection neurons (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in interstitial cells of Cajal, TRPC4 was suggested as a molecular candidate for the nonselective cation channel responsible for the pacemaker activity (14). In the entorhinal cortex, TRPC cation channels mediating persistent muscarinic currents contribute significantly to the firing and mnemonic properties of projection neurons (44).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of TRPC4 (ENSG00000100991; TRPC4) is found in endothelium and smooth muscle cells (Beech 2005;Tiruppathi et al 2006), intestinal pacemaker cells (ICC) (Kim et al 2006), in many brain regions (Zechel et al 2007), adrenal glands (Philipp et al 2000), and in kidneys (Freichel et al 2005). It is suggested that TRPC4 is an essential component of the nonselective cation channel involved in neuromodulation of stomach smooth muscle after muscarinic stimulation (Lee et al 2005).…”
Section: Trpcsmentioning
confidence: 99%
“…In the murine small intestine, pacemaker potentials are predominantly induced by the activation of non-selective cation channels (25,26) or Cl -channels (27)(28)(29). To determine which channel is associated with the m-PM-induced depolarization of pacemaker potentials, the effects of m-PM on TRPM7 and Ca 2+ -activated Cl -channels were examined.…”
Section: Association Of Trpm7 and Camentioning
confidence: 99%
“…Additionally, endogenous agents are able to regulate GI motility function via ICCs (22)(23)(24)(25). Furthermore, transient receptor potential melastatin (TRPM) 7 (26) or Cl -channels, such as anoctamin1 (ANO1) (27)(28)(29), are associated with pacemaker potentials in the GI tract. Therefore, TRPM7 and ANO1 may be therapeutic targets for the treatment of GI motility disorders.…”
Section: Introductionmentioning
confidence: 99%